THE ROLE OF PROBIOTICS IN ENHANCING TOOTH HARDNESS AND MINERALIZATION IN CHILDREN (International journal of medical sciences, 2025)
Daily administration of probiotics has emerged as a promising approach to enhance oral health in children. This study aimed to evaluate the effect of Lactobacillus rhamnosus GG supplementation on enamel hardness and mineral content in primary teeth of children aged 4–9 years. A total of 60 children were randomly assigned to either a probiotic group, receiving daily chewable probiotic tablets for 12 weeks, or a control group following standard oral hygiene practices. Enamel hardness was measured using a portable hardness tester, and mineral content was assessed via Quantitative Light-Induced Fluorescence (QLF) at baseline, 6 weeks, and 12 weeks. Results demonstrated significant improvements in both enamel hardness and mineral content in the probiotic group compared to the control group (p < 0.01). No adverse events were reported. These findings indicate that probiotics are effective, safe, and non-invasive adjuncts in enhancing tooth hardness and mineralization, supporting preventive strategies in pediatric dentistry.